Exploration of a chemo-mechanical technique for the isolation of nanofibrillated cellulosic fiber from oil palm empty fruit bunch as a reinforcing agent in composites materials - Fatah, I.Y.A. (MDPI AG, 2014)
The aim of the present study was to determine the influence of sulphuric acid hydrolysis and high-pressure homogenization as an effective chemo-mechanical process for the isolation of quality nanofibrillated cellulose (NFC). The cellulosic fiber was isolated from oil palm empty fruit bunch (OPEFB) using acid hydrolysis methods and, subsequently, homogenized using a high-pressure homogenizer to produce NFC. The structural analysis and the crystallinity of the raw fiber and extracted cellulose were carried out by Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). The morphology and thermal stability were investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and thermogravimetric (TGA) analyses, respectively. The FTIR results showed that lignin and hemicellulose were removed effectively from the extracted cellulose nanofibrils. XRD analysis revealed that the percentage of crystallinity was increased from raw EFB to microfibrillated cellulose (MFC), but the decrease for NFC might due to a break down the hydrogen bond. The size of the NFC was determined within the 5 to 10nm. The TGA analysis showed that the isolated NFC had high thermal stability. The finding of present study reveals that combination of sulphuric acid hydrolysis and high-pressure homogenization could be an effective chemo-mechanical process to isolate cellulose nanofibers from cellulosic plant fiber for reinforced composite materials. Â© 2014 by the authors.